Upaya Guru PAI Dalam Meningkatkan Motivasi Siswa Mengikuti Program Tahfidz - Caniago, Maryam; Kosasih, Ahmad (Prodi Pendidikan Keagamaan Islam, 2023)
This research was motivated by the results of the Tahfidz activities at SMP Negeri 40 Padang which did not go well, this was due to the PAI teacher's strategy in increasing student motivation in participating in Tahfidz activities which had not been optimal. While the research method is a descriptive method with a qualitative approach. The sources of the research data were student representatives of SMP Negeri 40 Padang, representatives of the curriculum of SMP Negeri 40 Padang, Islamic religious education teachers for classes VII and VIII, Islamic religious education teachers for class IX. The data were obtained through observation, interviews, and documentation. The results of this study explain that the reasons for the lack of student motivation in participating in the Tahfidz program are that students come from schools with less religious teaching, students do not take part in additional learning activities such as studying at TPA where they live, lack of support and motivation from family, motivation to memorize Al - The Al-Qur’an is still lacking. Based on the research results, it can be categorized as teacher efforts in increasing student motivation in participating in tahfidz activities into inside learning and outside learning. While the teacher's efforts outside of learning are through tahfizh, muhadharah, advice and solicitation programs, communication with parents, and Al-Qur’an classes.